Venus’ light slab hinders its development of planetary-scale subduction - Junxing Chen; Hehe Jiang; Ming Tang; Jihua Hao; Meng Tian; Xu Chu (Nature Communications, 2022)
The simulation of slab buoyancy in 2-D models shows that Venus’ light slabs, due to a less eclogitized crust, experience more resistance to subduction. Thus, plate tectonics might have been more difficult to develop on Venus than on Earth.